Effect of thickness and ageing time on optical properties of Zinc oxide film using sol-gel method - Rashid A.R.A.; Kamarudin N.A.; Mohamad I.S.; Norizan M.N. (Universiti Malaysia Perlis (UniMAP), 2024)
International Journal of Nanoelectronics and Materials Volume 11 (Special Issue) Dec 2018 [187-194]